Self-temperature-limiting far-infrared carbon fiber conductive paper and preparation method thereof
By building a three-dimensional conductive network in far-infrared carbon fiber composite conductive paper and combining graphene and self-limiting temperature polymers, the problems of unstable conductive path and imperfect self-limiting temperature function are solved, and an efficient and safe self-limiting temperature effect is achieved.
Patent Information
- Application Number
- CN202511150608.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-18
- Publication Date
- 2025-10-17
AI Technical Summary
Existing far-infrared carbon fiber heating materials have unstable conductive paths, short service life, and safety hazards such as imperfect self-limiting temperature function.
A three-dimensional conductive network is constructed using short-cut carbon fibers, combined with a graphene mixture and a self-limiting temperature polymer to form a complete conductive network. The temperature self-limiting function is achieved through the expansion of the self-limiting temperature polymer.
A stable conductive path for the heating material is achieved, which increases the service life to more than 100,000 hours. The surface temperature uniformity and heat conversion efficiency are as high as 99%, with good safety and low electromagnetic radiation.
Smart Images

Figure CN120797458A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a carbon fiber conductive paper, in particular to a self-limiting temperature far infrared carbon fiber composite conductive paper and a preparation method thereof. BACKGROUND
[0002] The carbon fiber conductive paper should have excellent infrared performance, and the electric heating material prepared by using the carbon fiber conductive paper has high electric heating conversion efficiency, and the infrared radiation can generally reach more than 60%, which is widely used in floor heating, rehabilitation therapy, food drying, sterilization, wearable equipment, household appliances and other fields.
[0003] Chinese patent publication No. CN102226325A discloses a far infrared carbon fiber low temperature conductive heating paper. In this scheme, the paper pulp is beaten and then impregnated with carbon fibers treated by carbonization, water treatment and hydrophilic treatment. After homogenization and further beating, the mixed pulp is taken out to measure its resistance. The mixed pulp with a resistance error within 2%±10% is made into paper. Although this scheme solves the problems of hydrophobicity of carbon fibers and uneven dispersion in paper pulp, the heating element prepared by this scheme may overheat due to the inability to dissipate infrared heat during use, which may cause carbonization or breakdown of the heating body and surrounding decorations, or even cause fire and threaten personal safety.
[0004] Chinese patent publication No. CN113174097A discloses a self-limiting heating body. The self-limiting heating body is made of high-density polyethylene, nano-nickel powder, graphene, nano-conductive carbon black powder and particle-shaped high polymer. The added nano-nickel powder can make the resistance value of each part of the self-limiting heating body substantially equal, so that the temperature of the heating body is more uniform when powered. The added graphene and nano-conductive carbon black powder can improve the toughness, electrical conductivity and thermal conductivity of the self-limiting heating body. During the process of powering and heating of the self-limiting heating body, the particle-shaped high polymer will expand. When the temperature of the self-limiting heating body reaches the set maximum temperature, the particle-shaped high polymer expands to the maximum, thereby blocking the electrical connection between the nano-nickel powder, graphene and nano-conductive carbon black powder, and making the internal resistance of the heating body tend to infinity. At this time, the current of the heating body tends to be infinitely small, so that the temperature no longer rises, achieving the purpose of self-limiting temperature. Although this scheme achieves the purpose of self-limiting temperature, the conductive path is composed of nano-level nickel powder, conductive carbon black powder and graphene. With the increase of use time, the conductive path will decay, resulting in unstable conductive path. Generally, power decay will occur after 10,000 to 20,000 hours of use, which may cause breakdown and pose a great safety hazard. SUMMARY
[0005] In order to overcome the shortcomings of the prior art, the purpose of the present application is to provide a self-limiting temperature far infrared carbon fiber composite conductive paper and a preparation method thereof, which aims to solve the problem of low service life caused by unstable conductive path of existing far infrared heating materials by using short carbon fibers to build a stable conductive network, and at the same time has a self-limiting temperature function, and the far infrared electric heating material prepared by using the self-limiting temperature far infrared carbon fiber composite conductive paper will expand the carbon fiber conductive network when reaching the temperature limit, so as to stop heating and achieve the purpose of temperature limiting. The carbon fiber composite conductive paper of the present application can be widely used in building heating, rail transportation, aircraft equipment, wearable equipment, infrared physiotherapy and other planar far infrared electric heating elements.
[0006] The self-limiting temperature far infrared carbon fiber composite conductive paper of the present application is realized by the following technical scheme: a self-limiting temperature far infrared carbon fiber composite conductive paper, wherein the composite conductive paper is composed of shaped fibers, chopped carbon fibers, graphene mixture, self-limiting polymer and dispersant, the chopped carbon fibers build a three-dimensional conductive network in the shaped fibers, the graphene mixture and the self-limiting polymer adhered on the shaped fibers fill the three-dimensional conductive network built by the chopped carbon fibers, the three-dimensional conductive network includes a basic three-dimensional conductive network and an auxiliary three-dimensional conductive network, and the auxiliary three-dimensional conductive network fills the gaps in the basic three-dimensional conductive network, so that the self-limiting temperature far infrared carbon fiber composite conductive paper forms a complete conductive network and conductive path.
[0007] The self-limiting temperature far infrared carbon fiber composite conductive paper described above, wherein the composite conductive paper is composed of the following raw materials in mass percentage: shaped fibers 44%-91%, chopped carbon fibers 2.5%-40%, graphene mixture 1%-5%, self-limiting polymer 5%-10%, and dispersant 0.5%-1%.
[0008] The self-limiting temperature far infrared carbon fiber composite conductive paper described above, wherein the shaped fibers are composed of long fibers and short fibers, the length of the long fibers is 2-4.5 mm, the length of the short fibers is 0.5-1.5 mm, the long fibers and the short fibers are mixed according to a weight ratio of 2-4:1 and are subjected to beating, grinding and homogenization, and the shaped fibers can use one or a combination of wood fibers or chemical fibers.
[0009] The self-limiting temperature far infrared carbon fiber composite conductive paper described above, wherein the chopped carbon fibers use water-dispersible chopped carbon fibers, and the water-dispersible chopped carbon fibers use polyacrylonitrile-based carbon fibers treated by water dispersion with lengths of 0.5 mm, 1 mm, 2 mm, 3 mm and 4 mm, and the weight ratio of the above-mentioned chopped carbon fibers with lengths of 0.5 mm, 1 mm, 2 mm, 3 mm and 4 mm is 1:1:1-2.5:2-4:1.
[0010] The self-limiting temperature far infrared carbon fiber composite conductive paper, wherein the graphene mixture is mixed by a jet mill according to a weight ratio of 1:20-40:10-30 of graphene, graphite and conductive carbon black.
[0011] The self-limiting temperature far infrared carbon fiber composite conductive paper, wherein the self-limiting temperature polymer is combined according to a weight ratio of 1:1-3:0.2-0.5 of hot melt fiber, high molecular polymer and self-limiting temperature effect material; the hot melt fiber can be one or a combination of polyester fiber, copolyamide fiber, ethylene resin acetate fiber, polyethylene fiber or polypropylene fiber; the high molecular polymer is one or a combination of polyethylene glycol, polypropylene, polyethylene and polyvinylidene fluoride; the high molecular polymer is in a powder form with a particle size of 10-60 um; and the self-limiting temperature effect material is one or a combination of quartz, barium titanate or montmorillonite with a particle size of 5-50 um.
[0012] The self-limiting temperature far infrared carbon fiber composite conductive paper, wherein the dispersant is one or a combination of polyacrylamide and polyethylene oxide, and the polyacrylamide is preferably cationic polyacrylamide with a molecular weight of 16 million.
[0013] The carbon fiber composite conductive paper, wherein the water solution concentration of the dispersant is 0.5-2%.
[0014] A preparation method of a carbon fiber composite conductive paper, wherein the method comprises the following steps:
[0015] Step 1: beating the forming fiber;
[0016] Step 1.1: placing long fibers into a beater, soaking with hot water at 55-80℃ for 15-30 min, starting the beater to beat, beating time 30-90 min, beater speed 1200-1800 r / min;
[0017] Step 1.2: placing short fibers into the beater, soaking with hot water at 55-80℃ for 15-30 min, starting the beater to beat, beating time 30-90 min, beater speed 1200-1800 r / min;
[0018] Step 2: grinding and homogenizing the forming fiber;
[0019] Step 2.1: grinding the long fibers after beating in step 1.1;
[0020] Step 2.2: grinding the short fibers after beating in step 1.2;
[0021] Step 2.3: The milled long fibers and short fibers from step 2.1 and step 2.2 are fed into a homogenizer to homogenize the pulp to obtain a forming fiber slurry, the homogenizing time is 15-30 min, the rotation speed of the homogenizer is 800-1600 r / min.
[0022] Step 3: Preparation of an aqueous phase treated short carbon fiber solution;
[0023] Step 3.1: The water-dispersible short carbon fibers of 0.5 mm, 1 mm, 2 mm, 3 mm and 4 mm in length are weighed according to the proportion respectively;
[0024] Step 3.2: The dispersant is weighed according to the proportion;
[0025] Step 3.3: Start the homogenizer, inject 60-80°C pure water into the homogenizer container according to the dispersant solution concentration of 0.1%, the rotation speed of the homogenizer is 400-800 r / min;
[0026] Step 3.4: Dispersant dissolution heat treatment;
[0027] Step 3.4.1: The dispersant of 0.5 mm water-dispersible short carbon fibers obtained in step 3.2 is loaded into a funnel, the dispersant in the funnel is placed above the homogenizer container, and the dispersant in the funnel flows into the homogenizer container in step 3.3 for dispersant dissolution treatment, the dissolution time is 10-20 min;
[0028] Step 3.4.2: The dispersant of 1 mm water-dispersible short carbon fibers obtained in step 3.2 is loaded into a funnel, the dispersant in the funnel is placed above the homogenizer container, and the dispersant in the funnel flows into the homogenizer container in step 3.3 for dispersant dissolution treatment, the dissolution time is 10-20 min;
[0029] Step 3.4.3: The dispersant of 2 mm water-dispersible short carbon fibers obtained in step 3.2 is loaded into a funnel, the dispersant in the funnel is placed above the homogenizer container, and the dispersant in the funnel flows into the homogenizer container in step 3.3 for dispersant dissolution treatment, the dissolution time is 10-20 min;
[0030] Step 3.4.4: The dispersant of 3 mm water-dispersible short carbon fibers obtained in step 3.2 is loaded into a funnel, the dispersant in the funnel is placed above the homogenizer container, and the dispersant in the funnel flows into the homogenizer container in step 3.3 for dispersant dissolution treatment, the dissolution time is 10-20 min;
[0031] Step 3.4.5: The dispersant for 4mm water dispersible chopped carbon fiber obtained in step 3.2 is put into a funnel, the dispersant in the funnel is placed above the homogenizer container, the dispersant in the funnel flows into the homogenizer container of step 3.3 for dispersant dissolving treatment, the dissolving time is 10-20min;
[0032] Step 3.5: Water phase treatment of each length of chopped carbon fiber;
[0033] Step 3.5.1: The 0.5mm length of water dispersible chopped carbon fiber obtained in step 3.1 is put into the dispersant aqueous solution of step 3.4.1, the homogenization time is 15-20min, the homogenizer rotation speed is 1200-1600r / min, thereby obtaining a 0.5mm length of water phase treated carbon fiber solution;
[0034] Step 3.5.2: The 1mm length of water dispersible chopped carbon fiber obtained in step 3.1 is put into the dispersant aqueous solution of step 3.4.2, the homogenization time is 15-20min, the homogenizer rotation speed is 1200-1600r / min, thereby obtaining a 1mm length of water phase treated carbon fiber solution;
[0035] Step 3.5.3: The 2mm length of water dispersible chopped carbon fiber obtained in step 3.1 is put into the dispersant aqueous solution of step 3.4.3, the homogenization time is 10-20min, the homogenizer rotation speed is 1200-1600r / min, thereby obtaining a 2mm length of water phase treated carbon fiber solution;
[0036] Step 3.5.4: The 3mm length of water dispersible chopped carbon fiber obtained in step 3.1 is put into the dispersant aqueous solution of step 3.4.4, the homogenization time is 20-30min, the homogenizer rotation speed is 1200-1600r / min, thereby obtaining a 3mm length of water phase treated carbon fiber solution;
[0037] Step 3.5.5: The 4mm length of water dispersible chopped carbon fiber obtained in step 3.1 is put into the dispersant aqueous solution of step 3.4.5, the homogenization time is 20-40min, the homogenizer rotation speed is 1200-1600r / min, thereby obtaining a 4mm length of water phase treated carbon fiber solution.
[0038] Step 3.6: Preparation of a mixed solution of water phase treated chopped carbon fiber;
[0039] Step 3.6.1: The 1mm length of water phase treated carbon fiber solution obtained in step 3.5.2 and the 3mm length of water phase treated carbon fiber solution obtained in step 3.5.4 are mixed by homogenization, the homogenization time is 10-20min, the homogenizer rotation speed is 1200-1600r / min;
[0040] Step 3.6.2: The 2mm length of water phase treated carbon fiber solution obtained in step 3.5.3 is added into the homogenized solution in step 3.6.1, the homogenization time is 15-30min, and the homogenizer speed is 1200-1600r / min;
[0041] Step 3.6.3: The 4mm length of water phase treated carbon fiber solution obtained in step 3.5.5 is added into the homogenized solution in step 3.6.2, the homogenization time is 15-30min, and the homogenizer speed is 1400-1600r / min;
[0042] Step 3.6.4: The 0.5mm length of water phase treated carbon fiber solution obtained in step 3.5.1 is added into the homogenized solution in step 3.6.3, the homogenization time is 15-30min, and the homogenizer speed is 1400-1600r / min, thereby obtaining the water phase treated mixed solution of short carbon fibers.
[0043] Step 4: Preparation of graphene mixture;
[0044] Step 4.1: The graphene, graphite and conductive carbon black are weighed according to the ratio;
[0045] Step 4.2: The graphene, graphite and conductive carbon black obtained in step 4.1 are sent into an airflow pulverizer for mixing, and the mixing time is 15-30min, thereby obtaining the graphene mixture.
[0046] Step 5: The self-limiting polymer, hot melt fiber, macromolecular polymer and self-limiting effect material are weighed according to the ratio.
[0047] Step 6: Preparation of graphene mixture and forming fiber slurry
[0048] Step 6.1: The forming fiber slurry obtained in step 2.3 is pumped into the mixing tank, and the stirrer in the mixing tank is started, and the stirrer speed is 800-1200r / min;
[0049] Step 6.2: The graphene mixture obtained in step 4.2 is poured into the mixing tank for homogenization mixing, and the time is 15-30min;
[0050] Step 6.3: The steam pipe is placed in the mixing tank to heat the mixed solution in step 6.2, the steam temperature is 110-120℃, and the solution temperature in the mixing tank is heated to 70-90℃;
[0051] Step 6.4: The hot melt fiber obtained in step 5 is added into the mixed solution obtained in step 6.3 for homogenization mixing, and the time is 10-20min, thereby obtaining the graphene mixture and forming fiber mixed slurry.
[0052] Step 7: The high molecular polymer obtained in step 5 is added to the mixed pulp solution obtained in step 6.4 for homogenization mixing, for 5-15 minutes, the high molecular polymer is dissolved in the solution at 70-90℃ and adheres to the long or short fibers of the shaped fibers;
[0053] Step 8: The self-limiting temperature effect material obtained in step 5 is added to the mixed pulp solution completed in step 7 for homogenization mixing, for 10-15 minutes.
[0054] Step 9: The short carbon fiber aqueous phase treatment mixed solution obtained in step 3.6.4 is added to the mixed pulp solution in step 8 for pulp mixing homogenization, the pulp in the pulp tank is continuously heated by steam during the mixing homogenization, so that the temperature of the pulp solution is maintained at 70-80℃, and the homogenization time is 30-45 minutes.
[0055] Step 10: During the homogenization process, the mixed pulp is continuously extracted from the pulp tank in step 9 by a sheet former, and after the obtained sheet paper is hot-pressed and dried, the electrode is tied, and the resistance is measured multiple times, and the error of the resistance is within ±5%, thereby obtaining the pulp of the self-limiting temperature far infrared carbon fiber composite conductive paper.
[0056] Step 11: The mixed pulp with a resistance error of ±5% obtained in step 10 is used to obtain a self-limiting temperature far infrared carbon fiber composite conductive paper by a wet papermaking process.
[0057] The self-limiting temperature far infrared carbon fiber composite conductive paper and the preparation method thereof have the following advantages and positive effects compared with the prior art due to the adoption of the above scheme:
[0058] (1) The self-limiting temperature far infrared carbon fiber composite conductive paper has a whole surface of heating surface and heat dissipation surface, the surface temperature is uniform, and the working temperature can be adjusted according to actual needs within 50-120℃.
[0059] (2) The self-limiting temperature far infrared carbon fiber composite conductive paper has high thermal conversion efficiency of the heating body, the theoretical value of thermal efficiency is as high as 99%, the energy saving is 20%-30% higher than that of traditional surface or plate-shaped infrared materials, and the infrared radiation electric heating conversion efficiency can be as high as more than 75%, which is an advanced energy-saving material.
[0060] (3) The heat transfer of the self-limiting temperature far infrared carbon fiber composite conductive paper is mainly far infrared radiation, and it also releases 5-15μm far infrared light waves, activates water molecules in the human body, increases blood oxygen content, enhances cell vitality, improves human microcirculation, and promotes metabolism.
[0061] (4) The self-limiting temperature far infrared carbon fiber composite conductive paper product has a self-limiting temperature function, and when the far infrared heating material prepared by using the self-limiting temperature far infrared carbon fiber composite conductive paper reaches the temperature limiting temperature, the volume expansion of the self-limiting temperature polymer is used to reduce the contact number and gap size between the short carbon fiber and graphene mixture particles, so that the purpose of temperature limiting is achieved;
[0062] (5) The self-limiting temperature far infrared carbon fiber composite conductive paper has good electromagnetic compatibility, and the electromagnetic radiation EMF value is only 3%;
[0063] (6) The service life of the heating material prepared by using the self-limiting temperature far infrared carbon fiber composite conductive paper is up to 100,000 hours or more, and the leakage current is extremely low during use, and the safety is good. BRIEF DESCRIPTION OF DRAWINGS
[0064] Fig. 1 It is a structure schematic diagram of the self-limiting temperature far infrared carbon fiber composite conductive paper under a 200 times sem microscope.
[0065] Fig. 2 It is a carbon fiber conductive network structure schematic diagram of the self-limiting temperature far infrared carbon fiber composite conductive paper under a 1000 times sem microscope.
[0066] Fig. 3 It is a structure schematic diagram of the three-dimensional conductive network of the self-limiting temperature far infrared carbon fiber composite conductive paper.
[0067] Fig. 4 It is a preparation method flow chart of the self-limiting temperature far infrared carbon fiber composite conductive paper. DETAILED DESCRIPTION
[0068] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all the embodiments.
[0069] As Figs. 1 to 4As shown, the self-limiting temperature far infrared carbon fiber composite conductive paper of the present application is composed of shaped fibers, chopped carbon fibers, graphene mixture, self-limiting temperature polymer and dispersant. The chopped carbon fibers build a three-dimensional conductive network in the shaped fibers. The graphene mixture and self-limiting temperature polymer adhered on the shaped fibers fill the conductive network built by the chopped carbon fibers to form a complete three-dimensional conductive filling network structure. The three-dimensional conductive network includes a basic three-dimensional conductive network and an auxiliary three-dimensional conductive network. The auxiliary three-dimensional conductive network fills the gaps in the basic three-dimensional conductive network, so that the self-limiting temperature far infrared carbon fiber composite conductive paper forms a complete conductive network and conductive path. In operation, when the self-limiting temperature far infrared carbon fiber composite conductive paper reaches a limited temperature, the self-limiting temperature polymer expands to reduce the number of contact points of the conductive network built by the chopped carbon fibers, thereby increasing the resistance and achieving the purpose of self-limiting temperature.
[0070] The composite conductive paper is composed of the following raw materials in mass percentage: shaped fibers 44%-91%, chopped carbon fibers 2.5%-40%, graphene mixture 1%-5%, self-limiting temperature polymer 5%-10%, and dispersant 0.5%-1%.
[0071] The shaped fibers are composed of long fibers and short fibers. The length of the long fibers is 2-4.5 mm, and the length of the short fibers is 0.5-1.5 mm. The long fibers and short fibers are mixed according to a weight ratio of 2-4:1, and then are beaten, ground and homogenized. The shaped fibers can be wood fibers or chemical fibers, or a combination thereof.
[0072] The chopped carbon fibers are water-dispersible chopped carbon fibers. The water-dispersible chopped carbon fibers are polyacrylonitrile-based carbon fibers treated by water dispersion, and the lengths of the carbon fibers are 0.5 mm, 1 mm, 2 mm, 3 mm and 4 mm, respectively. The weight ratio of the carbon fibers with different lengths is 1:1:1-2.5:2-4:1.
[0073] The graphene mixture is composed of graphene, graphite and conductive carbon black, and the weight ratio of the three is 1:20-40:10-30. The mixture is obtained by a jet mill.
[0074] The self-limiting temperature polymer is composed of hot melt fibers, high molecular polymers and self-limiting temperature effect materials, and the weight ratio of the three is 1:1-3:0.2-0.5. The hot melt fibers can be polyester fibers, copolyamide fibers, ethylene resin acetate fibers, polyethylene fibers or polypropylene fibers, or a combination thereof. The high molecular polymers can be polyethylene glycol, polypropylene, polyethylene or polyvinylidene fluoride, or a combination thereof. The high molecular polymers are in powder form, and the particle size is 10-60 um. The self-limiting temperature effect materials can be quartz, barium titanate or montmorillonite, or a combination thereof. The particle size of the self-limiting temperature effect materials is 5-50 um.
[0075] The dispersant uses one or a combination of polyacrylamide or polyethylene oxide, the water solution concentration of the dispersant is 0.5-2%, and the polyacrylamide is preferably 16 million molecular weight cationic polyacrylamide.
[0076] A preparation method of a carbon fiber composite conductive paper, wherein the method comprises the following steps:
[0077] Step 1: beating the forming fibers;
[0078] Step 1.1: Put the long fibers into the beater, soak them in hot water at 55-80℃ for 15-30min, start the beater for beating, the beating time is 30-90min, and the beater speed is 1200-1800r / min;
[0079] Step 1.2: Put the short fibers into the beater, soak them in hot water at 55-80℃ for 15-30min, start the beater for beating, the beating time is 30-90min, and the beater speed is 1200-1800r / min;
[0080] Step 2: refining and homogenizing the forming fibers;
[0081] Step 2.1: refining the long fibers after beating in step 1.1;
[0082] Step 2.2: refining the short fibers after beating in step 1.2;
[0083] Step 2.3: sending the refined long fibers and short fibers obtained in steps 2.1 and 2.2 into the homogenizer for homogenizing and mixing to obtain the forming fiber slurry, the homogenizing and mixing time is 15-30min, and the homogenizer speed is 800-1600r / min.
[0084] Step 3: preparing an aqueous phase treated short carbon fiber solution;
[0085] Step 3.1: weighing the water-dispersible short carbon fibers with lengths of 0.5mm, 1mm, 2mm, 3mm and 4mm according to the proportions;
[0086] Step 3.2: weighing the dispersant according to the proportions;
[0087] Step 3.3: starting the homogenizer, injecting 60-80℃ pure water into the homogenizer container according to the dispersant solution concentration of 0.1%, and the homogenizer speed is 400-800r / min;
[0088] Step 3.4: dispersant solution heat treatment;
[0089] Step 3.4.1: The dispersant of 0.5mm water dispersible chopped carbon fiber obtained from step 3.2 is put into a funnel, and the dispersant in the funnel is placed above the homogenizer container, the dispersant in the funnel flows into the homogenizer container of step 3.3 for dispersant dissolution treatment, and the dissolution time is 10-20min;
[0090] Step 3.4.2: The dispersant of 1mm water dispersible chopped carbon fiber obtained from step 3.2 is put into a funnel, and the dispersant in the funnel is placed above the homogenizer container, the dispersant in the funnel flows into the homogenizer container of step 3.3 for dispersant dissolution treatment, and the dissolution time is 10-20min;
[0091] Step 3.4.3: The dispersant of 2mm water dispersible chopped carbon fiber obtained from step 3.2 is put into a funnel, and the dispersant in the funnel is placed above the homogenizer container, the dispersant in the funnel flows into the homogenizer container of step 3.3 for dispersant dissolution treatment, and the dissolution time is 10-20min;
[0092] Step 3.4.4: The dispersant of 3mm water dispersible chopped carbon fiber obtained from step 3.2 is put into a funnel, and the dispersant in the funnel is placed above the homogenizer container, the dispersant in the funnel flows into the homogenizer container of step 3.3 for dispersant dissolution treatment, and the dissolution time is 10-20min;
[0093] Step 3.4.5: The dispersant of 4mm water dispersible chopped carbon fiber obtained from step 3.2 is put into a funnel, and the dispersant in the funnel is placed above the homogenizer container, the dispersant in the funnel flows into the homogenizer container of step 3.3 for dispersant dissolution treatment, and the dissolution time is 10-20min;
[0094] Step 3.5: Water phase treatment of chopped carbon fibers of various lengths;
[0095] Step 3.5.1: The 0.5mm length of water dispersible chopped carbon fiber obtained from step 3.1 is put into the dispersant aqueous solution of step 3.4.1, and the homogenization time is 15-20min, and the homogenizer speed is 1200-1600r / min, thereby obtaining a 0.5mm length of water phase treated carbon fiber solution;
[0096] Step 3.5.2: The 1mm length of water dispersible chopped carbon fiber obtained from step 3.1 is put into the dispersant aqueous solution of step 3.4.2, and the homogenization time is 15-20min, and the homogenizer speed is 1200-1600r / min, thereby obtaining a 1mm length of water phase treated carbon fiber solution;
[0097] Step 3.5.3: Put the 2mm length of water dispersible short-cut carbon fiber obtained from step 3.1 into the dispersant aqueous solution of step 3.4.3, homogenize for 10-20 minutes at 1200-1600r / min, to obtain a 2mm length of water phase treated carbon fiber solution;
[0098] Step 3.5.4: Put the 3mm length of water dispersible short-cut carbon fiber obtained from step 3.1 into the dispersant aqueous solution of step 3.4.4, homogenize for 20-30 minutes at 1200-1600r / min, to obtain a 3mm length of water phase treated carbon fiber solution;
[0099] Step 3.5.5: Put the 4mm length of water dispersible short-cut carbon fiber obtained from step 3.1 into the dispersant aqueous solution of step 3.4.5, homogenize for 20-40 minutes at 1200-1600r / min, to obtain a 4mm length of water phase treated carbon fiber solution.
[0100] The water dispersible short-cut carbon fiber, although having been hydrophilic treated, is affected by length when dispersed, the longer the length of the short-cut carbon fiber, the more difficult to disperse, generally 0.5-2mm length of water dispersible short-cut carbon fiber is easier to disperse, while more than 2mm length is more difficult to disperse, so the homogenization time is increased to improve the dispersion.
[0101] Step 3.6: Prepare a water phase treated mixed solution of short-cut carbon fiber;
[0102] Step 3.6.1: Homogenize the 1mm length of water phase treated carbon fiber solution obtained from step 3.5.2 and the 3mm length of water phase treated carbon fiber solution obtained from step 3.5.4, homogenize for 10-20 minutes at 1200-1600r / min;
[0103] Step 3.6.2: Add the 2mm length of water phase treated carbon fiber solution obtained from step 3.5.3 to the homogenized solution of step 3.6.1, homogenize for 15-30 minutes at 1200-1600r / min;
[0104] Step 3.6.3: Add the 4mm length of water phase treated carbon fiber solution obtained from step 3.5.5 to the homogenized solution of step 3.6.2, homogenize for 15-30 minutes at 1400-1600r / min;
[0105] Step 3.6.4: The water phase treated carbon fiber solution of 0.5mm length obtained from step 3.5.1 is added into the homogeneous solution of step 3.6.3, and the homogeneous time is 15-30min, and the speed of the homogenizer is 1400-1600r / min, so as to obtain the water phase treated mixed solution of the chopped carbon fiber.
[0106] The water phase treated carbon fiber is uniformly dispersed, but when the carbon fibers of different lengths are mixed, the flocculation is prone to occur, especially the chopped carbon fiber of length more than 2mm is prone to flocculation when mixed. It is found through batch production test that the water phase treated carbon fiber solution of 1mm length and the water phase treated carbon fiber solution of 3mm length are first mixed by homogenization, and the carbon fibers of different lengths are uniformly dispersed in the solution, which is mainly that the 1mm length of the chopped carbon fiber continuously impacts and combs the 3mm length of the carbon fiber in the solution. Under the impact and combing of the 1mm length of the chopped carbon fiber, the 3mm length of the chopped carbon fiber is uniformly dispersed in the mixed solution. Then the water phase treated carbon fiber solution of 2mm and 4mm length is added in turn. According to the above principle, the carbon fibers of different lengths impact and comb each other in the solution, so as to avoid the flocculation of the carbon fiber. Finally, the water phase treated carbon fiber solution of 0.5mm length is added to impact and comb the carbon fiber in the mixed solution of the water phase treated carbon fiber of the above four lengths, so as to ensure the uniform dispersion of the carbon fiber in the solution and avoid the flocculation of the carbon fiber of long length.
[0107] Step 4: Preparation of graphene mixture;
[0108] Step 4.1: The graphene, graphite and conductive carbon black are weighed according to the ratio;
[0109] Step 4.2: The graphene, graphite and conductive carbon black obtained from step 4.1 are sent into the jet mill for mixing, and the mixing time is 15-30min, so as to obtain the graphene mixture.
[0110] Step 5: The self-limiting polymer, hot melt fiber, polymer and self-limiting effect material are weighed according to the ratio.
[0111] Step 6: Preparation of graphene mixture and forming fiber slurry
[0112] Step 6.1: The forming fiber slurry obtained from step 2.3 is pumped into the mixing pool, and the stirrer in the mixing pool is started, and the speed of the stirrer is 800-1200r / min;
[0113] Step 6.2: The graphene mixture obtained from step 4.2 is poured into the mixing pool for homogeneous mixing, and the time is 15-30min;
[0114] Step 6.3: Put the steam pipe into the mixing tank to heat the mixed solution of step 6.2, the steam temperature is 110-120℃, and the solution temperature in the mixing tank is heated to 70-90℃;
[0115] Step 6.4: Add the hot melt fiber obtained in step 5 to the mixed solution obtained in step 6.3 to homogenously mix, the time is 10-20min, so as to obtain a mixed slurry of graphene mixture and forming fiber.
[0116] The hot melt fiber can quickly dissolve in the water solution heated to 70-90℃, and the hot melt fiber dissolved in water can effectively adhere the graphene mixture to the long fibers or short fibers of the forming fiber, ensuring that the conductive paper formed by the papermaking forms a stable three-dimensional conductive filling network structure.
[0117] The self-limiting temperature far infrared carbon fiber composite conductive paper takes the forming fiber as the matrix, and builds a three-dimensional conductive network by uniformly dispersing and mixing the short carbon fibers in the forming fiber. The conductive network is built by carbon fibers with lengths of 3mm and 4mm to form a basic three-dimensional conductive network, and 0.5mm, 1mm and 2mm carbon fibers fill the gaps in the basic three-dimensional conductive network skeleton and form an auxiliary three-dimensional conductive network, so as to ensure the formation of a "basic three-dimensional conductive network + auxiliary three-dimensional conductive network" structure. The carbon fiber composite conductive paper belongs to a planar heating material, and the existing technology is a basic three-dimensional conductive network structure. The gaps in the basic three-dimensional conductive network structure are not filled with carbon fibers, and the surface temperature difference in these areas is too large, which causes high energy consumption and other problems. By using the "basic three-dimensional conductive network + auxiliary three-dimensional conductive network" structure, the auxiliary three-dimensional conductive network fills the gaps in the basic three-dimensional conductive network, so that the entire surface of the carbon fiber composite conductive paper is filled with the basic three-dimensional conductive network structure skeleton, so that the entire surface of the prepared heating material is a heating surface. Since the auxiliary three-dimensional conductive network fills the gaps in the basic three-dimensional conductive network, there are no gaps in the entire heating surface in the microstructure, so the heating is uniform, the temperature difference is small, and the energy consumption is low.
[0118] Step 7: Add the high molecular polymer obtained in step 5 to the mixed slurry solution obtained in step 6.4 to homogenously mix, the time is 5-15min, and the high molecular polymer is dissolved in the solution at 70-90℃ and adheres to the long fibers or short fibers of the forming fiber;
[0119] Step 8: Add the self-limiting temperature effect material obtained in step 5 to the mixed slurry solution completed in step 7 to homogenously mix, the time is 10-15min.
[0120] Step 9: The short-cut carbon fiber water phase treatment mixed solution obtained in step 3.6.4 is added to the mixed pulp solution of step 8 for homogenization and dispersion. The pulp in the pulp tank is continuously heated by steam to maintain the temperature of the pulp solution at 70-80°C, and the homogenization time is 30-45 min.
[0121] The self-limiting temperature far infrared carbon fiber composite conductive paper conforms to the conductive chain and thermal expansion model and the tunnel conductive model. The short-cut carbon fibers in the self-limiting temperature far infrared carbon fiber composite conductive paper directly contact to form a three-dimensional conductive network. The graphene mixture particles adhered to the formed fibers in the self-limiting temperature far infrared carbon fiber composite conductive paper directly contact each other to fill and supplement the continuous conductive network formed by the three-dimensional conductive network of the short-cut carbon fibers, so that the self-limiting temperature far infrared carbon fiber composite conductive paper forms a complete conductive network and conductive path. Generally speaking, when the short-cut carbon fibers and the graphene mixture particles contact each other to form a chain network, i.e., a three-dimensional conductive filling network, the more the network particles in contact, the denser the network, and the smaller the gap between the particles, the higher the electrical conductivity. According to the "conductive channel" theory, only when a complete conductive continuous network is formed, i.e., when the gap between the conductive particles is very small, will the conductive phenomenon occur. Therefore, the main factors affecting the electrical conductivity σ include the number of contacts, the contact resistance, and the gap size. Therefore, by changing the number of contacts and the gap size between the short-cut carbon fibers and the graphene mixture particles in the self-limiting temperature far infrared carbon fiber composite conductive paper, the electrical conductivity can be improved or reduced. The "tunnel effect" believes that the conductive network is still formed, but the conductive particles are not directly in contact to conduct electricity, but rely on the migration of electrons between the conductive particles caused by thermal vibration. Tunneling only occurs between very close filler aggregates, and there is no conduction between aggregates with large gaps. Tunneling believes that there is a close relationship between electrical conductivity and temperature, and the thermal excitation voltage increases the electrical conductivity. At the beginning, the conductive particles form conductive chains in the polymer. When the temperature rises, the volume of the polymer matrix expands, and because the expansion rates of the matrix and the conductive chains are different, the conductive chains are slowly separated, and the resistance increases. At the melting point, the volume of the polymer suddenly increases, the conductive chains are broken, and the resistance also suddenly increases, i.e., the composite system exhibits PTC phenomenon. Therefore, the self-limiting temperature far infrared carbon fiber composite conductive paper adjusts the number of contacts and the gap size between the short-cut carbon fibers and the graphene mixture particles through the volume expansion of the self-limiting polymer, thereby achieving the PTC purpose.
[0122] Step 10: During the homogenization process, the mixed pulp is continuously extracted from the pulp tank in step 9, and the obtained sheet paper is dried by hot pressing and then measured for resistance multiple times. The error of the multiple resistance measurements is within ±5%, and the pulp for preparing the self-limiting temperature far infrared carbon fiber composite conductive paper is obtained.
[0123] Step 11: the mixed slurry with resistance error of ±5% obtained in step 10 is used to obtain a self-limiting temperature far infrared carbon fiber composite conductive paper by a wet papermaking process.
[0124] The product manufactured by the self-limiting temperature far infrared carbon fiber composite conductive paper of the present application has a self-limiting temperature function, and the far infrared electric heating material prepared by using the self-limiting temperature far infrared carbon fiber composite conductive paper of the present application can achieve the purpose of limiting temperature by the volume expansion of the self-limiting temperature polymer to reduce the contact number and gap size between the short carbon fiber and graphene mixture particles when the far infrared electric heating material reaches the limiting temperature.
[0125] In the description of the present application, it should be understood that the terms "center", "longitudinal", "transverse", "length", "width", "thickness", "upper", "lower", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", "clockwise", "counterclockwise" and the like indicate the orientation or positional relationship based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, and therefore cannot be understood as indicating or implying that the devices or elements indicated must have a particular orientation, be constructed and operated in a particular orientation, and therefore cannot be understood as limiting the present application.
[0126] In addition, the terms "first", "second" are only for the purpose of description, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the technical features indicated. Therefore, the features defined with "first", "second" can explicitly or implicitly include one or more of the features. In the description of the present application, the meaning of "multiple" is two or more, unless otherwise specifically limited.
[0127] The above is only a preferred specific embodiment of the present application, but the protection scope of the present application is not limited thereto, and any person skilled in the art can make equivalent replacement or change according to the technical solution and the inventive concept of the present application within the technical range disclosed by the present application, which should be covered within the protection scope of the present application.
Claims
1. A self-limiting temperature far-infrared carbon fiber composite conductive paper, characterized in that: The composite conductive paper is composed of molded fibers, chopped carbon fibers, a graphene mixture, a self-limiting temperature polymer and a dispersant. The chopped carbon fibers form a three-dimensional conductive network in the molded fibers. The graphene mixture and the self-limiting temperature polymer bonded to the molded fibers fill the three-dimensional conductive network constructed by the chopped carbon fibers. The three-dimensional conductive network includes a basic three-dimensional conductive network and an auxiliary three-dimensional conductive network. The auxiliary three-dimensional conductive network fills the gaps in the basic three-dimensional conductive network, thereby forming a complete conductive network and conductive path for the self-limiting temperature far-infrared carbon fiber composite conductive paper.
2. The self-temperature-limiting far-infrared carbon fiber composite conductive paper according to claim 1, characterized in that: The composite conductive paper is composed of the following raw materials in percentage by mass: 44%-91% of formed fiber, 2.5%-40% of chopped carbon fiber, 1%-5% of graphene mixture, 5%-10% of self-temperature limiting polymer, and 0.5%-1% of dispersant.
3. The self-temperature-limiting far-infrared carbon fiber composite conductive paper according to claim 1, characterized in that: The shaped fibers are formed by mixing long fibers and short fibers. The length of the long fibers is 2-4.5 mm, and the length of the short fibers is 0.5-1.5 mm. The long fibers and short fibers are pulped, refined, and homogenized in a weight ratio of 2-4:
1. The shaped fibers are made of one or a combination of wood fibers or chemical fibers.
4. The self-temperature-limiting far-infrared carbon fiber composite conductive paper according to claim 1, characterized in that: The chopped carbon fibers are water-dispersible chopped carbon fibers, which are water-dispersible polyacrylonitrile carbon fibers with lengths of 0.5 mm, 1 mm, 2 mm, 3 mm and 4 mm, respectively. The weight ratio of the chopped carbon fibers with lengths of 0.5 mm, 1 mm, 2 mm, 3 mm and 4 mm is 1:1:1-2.5:2-4:
1.
5. The self-temperature-limiting far-infrared carbon fiber composite conductive paper according to claim 1, characterized in that: The graphene mixture is prepared by mixing graphene, graphite and conductive carbon black in a weight ratio of 1:20-40:10-30 through a jet mill.
6. The self-temperature-limiting far-infrared carbon fiber composite conductive paper according to claim 1, characterized in that: The self-limiting temperature polymer is composed of a thermo-fusible fiber, a high molecular polymer and a self-limiting temperature effect material in a weight ratio of 1:1-3:0.2-0.
5. The thermo-fusible fiber adopts one or a combination of polyester fiber, copolyamide fiber, ethylene resin acetate fiber, polyethylene fiber or polypropylene fiber. The high molecular polymer adopts one or a combination of polyethylene glycol, polypropylene, polyethylene, and polyvinylidene fluoride. The high molecular polymer is in powder form with a particle size of 10-60um. The self-limiting temperature effect material adopts one or a combination of quartz stone, barium titanate or montmorillonite. The particle size of the self-limiting temperature effect material is 5-50um.
7. The self-temperature-limiting far-infrared carbon fiber composite conductive paper according to claim 1, characterized in that: The dispersant is polyacrylamide or polyethylene oxide or a combination thereof, and the concentration of the aqueous solution of the dispersant is 0.5-2%.
8. The self-temperature-limiting far-infrared carbon fiber composite conductive paper according to claim 7, characterized in that: The polyacrylamide is a cationic polyacrylamide with a molecular weight of 16 million.
9. A method for preparing carbon fiber composite conductive paper, characterized in that: The method comprises at least the following steps: Step 1: Beating the formed fibers; Step 2: Refining and homogenizing the formed fibers; Step 3: preparing an aqueous phase treated chopped carbon fiber solution; Step 4: preparing a graphene mixture; Step 5: Weigh the hot-melt fiber, high molecular polymer and self-limiting temperature effect material in the self-limiting temperature polymer according to the ratio; Step 6: preparing a graphene mixture and a molded fiber slurry; Step 7: Add the high molecular weight polymer obtained in step 5 to the mixed slurry solution obtained in step 6 and mix them homogeneously for 5-15 minutes; the high molecular weight polymer dissolves in the solution at 70-90°C and adheres to the long fibers or short fibers of the molded fibers; Step 8: Add the self-temperature limiting effect material obtained in step 5 to the mixed slurry solution completed in step 7 and mix them homogeneously for 10-15 minutes; Step 9: Add the aqueous treatment mixed solution of the chopped carbon fiber obtained in step 3 to the mixed slurry solution in step 8 for mixing and homogenizing. During the mixing and homogenization, continue to steam heat the slurry in the slurry pool to keep the slurry solution temperature at 70-80°C, and the homogenization time is 30-45 minutes. Step 10: During the homogenization process, the mixed slurry is continuously extracted from the slurry pool in step 9 and paper is made using a sheet making machine. The obtained paper sheets are hot-pressed and dried, and then electrodes are inserted and the resistance is measured multiple times. If the resistance error of the multiple measurements is within ±5%, the slurry for preparing the self-temperature-limiting far-infrared carbon fiber composite conductive paper is obtained; Step 11: The mixed slurry obtained in step 10 with a resistance error of ±5% is subjected to a wet papermaking process to obtain a self-limiting temperature far-infrared carbon fiber composite conductive paper.
10. The method for preparing carbon fiber composite conductive paper according to claim 9, wherein: Step 1 also includes the following steps: Step 1.1: Place the long fiber into a pulping machine and soak it in hot water at 55-80°C for 15-30 minutes. Start the pulping machine for 30-90 minutes at a speed of 1200-1800 r / min. Step 1.2: Put the short fibers into a beater and soak them in hot water at 55-80°C for 15-30 minutes. Start the beater for beating. The beating time is 30-90 minutes and the beater speed is 1200-1800 r / min.
11. The method for preparing carbon fiber composite conductive paper according to claim 10, wherein: Step 2 also includes the following steps: Step 2.1: Refining the long fibers after beating in step 1.1; Step 2.2: refining the short fibers after being beaten in step 1.2; Step 2.3: The long fibers and short fibers obtained after refining in step 2.1 and step 2.2 are fed into a homogenizer for homogenization and mixing to obtain a formed fiber slurry. The homogenization and mixing time is 15-30 minutes, and the speed of the homogenizer is 800-1600 r / min.
12. The method for preparing carbon fiber composite conductive paper according to claim 11, wherein: Step 3 also includes the following steps: Step 3.1: Weigh water-dispersible chopped carbon fibers of 0.5 mm, 1 mm, 2 mm, 3 mm, and 4 mm in length according to the ratio; Step 3.2: Weigh the dispersant according to the ratio; Step 3.3: Start the homogenizer and inject 60-80°C purified water into the homogenizer container according to the dispersant solution concentration of 0.1%. The homogenizer speed is 400-800 r / min; Step 3.4: Dispersant dissolution heat treatment; Step 3.4.1: Place the dispersant of 0.5 mm water-dispersible chopped carbon fiber obtained in step 3.2 into a funnel, place the dispersant in the funnel above the homogenizer container, and let the dispersant in the funnel flow into the homogenizer container in step 3.3 for dissolution of the dispersant. The dissolution time is 10-20 minutes. Step 3.4.2: Place the 1 mm water-dispersible chopped carbon fiber dispersant obtained in step 3.2 into a funnel, place the dispersant in the funnel above the homogenizer container, and flow the dispersant in the funnel into the homogenizer container in step 3.3 for dissolution of the dispersant. The dissolution time is 10-20 minutes. Step 3.4.3: Place the dispersant of 2 mm water-dispersible chopped carbon fiber obtained in step 3.2 into a funnel, place the dispersant in the funnel above the homogenizer container, and let the dispersant in the funnel flow into the homogenizer container in step 3.3 for dissolution of the dispersant. The dissolution time is 10-20 minutes. Step 3.4.4: Place the dispersant of 3mm water-dispersible chopped carbon fiber obtained in step 3.2 into a funnel, place the dispersant in the funnel above the homogenizer container, and let the dispersant in the funnel flow into the homogenizer container in step 3.3 for dissolution treatment. The dissolution time is 10-20 minutes. Step 3.4.5: Place the dispersant of 4 mm water-dispersible chopped carbon fiber obtained in step 3.2 into a funnel, place the dispersant in the funnel above the homogenizer container, and let the dispersant in the funnel flow into the homogenizer container in step 3.3 for dissolution of the dispersant. The dissolution time is 10-20 minutes. Step 3.5: Aqueous treatment of chopped carbon fibers of various lengths; Step 3.5.1: Add the 0.5 mm long water-dispersible chopped carbon fiber obtained in step 3.1 to the dispersant aqueous solution in step 3.4.1, and homogenize for 15-20 minutes at a homogenizer speed of 1200-1600 rpm to obtain a 0.5 mm long water-treated carbon fiber solution; Step 3.5.2: Add the 1 mm long water-dispersible chopped carbon fibers obtained in step 3.1 to the dispersant aqueous solution in step 3.4.2 and homogenize for 15-20 minutes at a homogenizer speed of 1200-1600 rpm to obtain a 1 mm long aqueous-treated carbon fiber solution. Step 3.5.3: Add the 2 mm long water-dispersible chopped carbon fibers obtained in step 3.1 to the dispersant aqueous solution obtained in step 3.4.3 and homogenize for 10-20 minutes at a homogenizer speed of 1200-1600 rpm to obtain a 2 mm long aqueous-treated carbon fiber solution. Step 3.5.4: Add the 3 mm long water-dispersible chopped carbon fibers obtained in step 3.1 to the dispersant aqueous solution in step 3.4.4 and homogenize for 20-30 minutes at a homogenizer speed of 1200-1600 rpm to obtain a 3 mm long aqueous-treated carbon fiber solution. Step 3.5.5: Add the 4 mm long water-dispersible chopped carbon fibers obtained in step 3.1 to the dispersant aqueous solution in step 3.4.5 and homogenize for 20-40 minutes at a homogenizer speed of 1200-1600 rpm to obtain a 4 mm long aqueous-treated carbon fiber solution. Step 3.6: preparing a mixed solution for aqueous treatment of chopped carbon fibers; Step 3.6.1: Homogenize the 1 mm long water-treated carbon fiber solution obtained in step 3.5.2 and the 3 mm long water-treated carbon fiber solution obtained in step 3.5.4 for 10-20 minutes at a homogenizer speed of 1200-1600 rpm. Step 3.6.2: Add the 2 mm long aqueous carbon fiber solution obtained in step 3.5.3 to the homogenized solution in step 3.6.
1. Homogenize for 15-30 min at a homogenizer speed of 1200-1600 rpm. Step 3.6.3: Add the 4 mm long aqueous carbon fiber solution obtained in step 3.5.5 to the homogenized solution in step 3.6.
2. Homogenize for 15-30 minutes at a homogenizer speed of 1400-1600 rpm. Step 3.6.4: The 0.5 mm long water-treated carbon fiber solution obtained in step 3.5.1 is added to the homogenized solution in step 3.6.
3. The homogenization time is 15-30 minutes, and the homogenizer speed is 1400-1600 r / min, thereby obtaining a short-cut carbon fiber water-treated mixed solution.
13. The method for preparing carbon fiber composite conductive paper according to claim 12, wherein: Step 4 also includes the following steps: Step 4.1: Weigh graphene, graphite, and conductive carbon black in a weight ratio of 1:20-40:10-30; Step 4.2: The graphene, graphite and conductive carbon black obtained in step 4.1 are fed into a jet mill for mixing for 15-30 minutes to obtain a graphene mixture.
14. The method for preparing carbon fiber composite conductive paper according to claim 13, wherein: Step 6 also includes the following steps: Step 6.1: Pump the formed fiber slurry obtained in step 2.3 into a mixing tank, and start the mixer in the mixing tank at a speed of 800-1200 r / min; Step 6.2: Pour the graphene mixture obtained in step 4.2 into a mixing tank for homogenous mixing for 15-30 minutes; Step 6.3: Place the steam pipe into the mixing tank to heat the mixed solution in step 6.2, with the steam temperature at 110-120°C, and heat the solution temperature in the mixing tank to 70-90°C; Step 6.4: Add the hot-melt fiber obtained in step 5 to the mixed solution obtained in step 6.3 and mix them homogeneously for 10-20 minutes to obtain a mixed slurry of graphene mixture and molded fiber.
Citation Information
Patent Citations
Far infrared carbon fiber low temperature conductive heating paper and preparation method thereof
CN102226325A
Self-temperature-limiting heating body and manufacturing method thereof and self-temperature-limiting heating sheet
CN113174097A